PENINGKATAN KETERAMPILAN MENULIS TEKS ULASAN MENGGUNAKAN MEDIA AUDIOVISUAL PADA SISWA KELAS VIII SMP - Cornelia, Fransiska; Salem, Laurensius; Sukamto, Sukamto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis reseach aims to improve review text writing skills using audio visual media in grade VIII SMP. The particular problem is how to improve students' writing text skills in finding content structure, linguistic characteristics and the results of writing a review text. The purpose of this study is to describe the research problem. The method and form of research used are qualitative descriptions. The research data were 28 students in class VIII. The results of this study indicate the results of an increase in writing a review text using audio visual media in the first cycle using audiovisual media with an average value of 61.80. The average value in the second cycle with an average of 71.538.Based on student writing result data, from cycle I to cycle II also increased.The value of student learning outcomes before using audiovisual media with an average of 56.15.Keywords: Audiovisual Media, Review Text, Writing